Co9S8 quasi-hexagonal nanoparticles coupled with WS2 nanoring anchored on 3D sulfur, nitrogen Co-doped carbon nanotubes@graphene oxide cross-linking architecture for high performance asymmetric supercapacitor. (15th April 2022) - Li, Yujin; Liu, Lian; Yu, Yadi; Shang, Xueni; Meng, Fanbin
Abstract: Designing advanced hybrid supercapacitors (SCs) electrode materials with 3D cross-linking hierarchical porous architecture has desirable structural advantages, which can facilitate ion transport and provide excellent reaction site. Herein, a unique nanostructure consisting of Co9 S8 quasi-hexagonal nanoparticles coupled with WS2 nanoring anchored on 3D sulfur, nitrogen Co-doped carbon nanotubes@graphene oxide (Co9 S8 @WS2 -NS-15mlGO@CNTs) was obtained using a facile solvothermal strategy. This cross-linking and hierarchical porous nanostructure can maximize the electrical conductivity of entirety, which provides a favorable transport and permeability for the ions and electrons of the electrolyte environment. Benefiting from the structural compositional advantages and full play of the synergetic coupling effect, the as-prepared Co9 S8 @WS2 -NS-15mlGO@CNTs electrode material exhibits absolutely the topmost specific capacitance of 1820.8 F g −1 at a current density of 1 A g −1 and outstanding cycle stability with a capacitance retention of 90.2% after 10000 cycles at 30 A g −1 . Moreover, an asymmetric supercapacitor (ASC) fabricated by Co9 S8 @WS2 -NS-15mlGO@CNTs (positive electrode) and NS-15mlGO@CNTs (negative electrode) presents an ultra-high energy density of 95.3 Wh kg −1  at a power density of 600 W kg −1, and long cycle life with 86.7% specific capacity retention at a current density of 20 A g −1 after 10000 cycles. It is believed that the presented work may open a new perspective to fabricate future competitive high-performance energy storage devices. Graphical abstract: Image 1 Highlights: Co9 S8 coupled with WS2 anchored on sulfur, nitrogen Co-doped carbon nanotubes@graphene oxide was obtained. The as-prepared Co9 S8 @WS2 -NS-15mlGO@CNTs electrode material exhibits the specific capacitance of 1820.8 Fg -1 at a current density of 1 A g −1 . The fabricated ASC device presents an ultra-high energy density of 95.3 Wh kg −1  at a power density of 600 W kg −1 . The energy density is remarkably superior to those of the previous reported carbon ASC devices.